Cholera public health surveillance in the Republic of Cameroon-opportunities and challenges - Ngwa, Moise Chi (Pan Afr Med J, 2016)
INTRODUCTION: In Cameroon, cholera has periodically resurfaced since it was first reported in 1971. In 2003, Cameroon adapted the Integrated Disease Surveillance and Response (IDSR) strategy to strengthen surveillance in the country. This study was an in-depth description and assessment of the structure, core and support functions, and attributes of the current cholera surveillance system in Cameroon. It also discussed its strengths and challenges with hope that lessons learned could improve the system in Cameroon and in other countries in Africa implementing the IDSR strategy. METHODS: Semi-structured key informant interviews, peer reviewed articles, and government record review were conducted in the Far North and Centre Regions of Cameroon. We used the matrix and conceptual framework from the World Health Organization (WHO) and Centers for Disease Control and Prevention, WHO Regional Office for Africa Technical Guidelines to frame the study. Site visits included the WHO country office, the ministry of public health (MoPH), two Regional Public Health Delegations (RPHDs), eight health districts (HDs) and health facilities (HFs) including two labs. RESULTS: Cholera surveillance is passive but turns active during outbreaks and follows a hierarchical structure. Cholera data are collected at HFs and sent to HDs where data are compiled and sent to the RPHD in paper format. RPHDs de-identify, digitalize, and send the data to the MoPH via internet and from there to the WHO. The case definition was officially changed in 2010 but the outdated definition was still in use in 2013. Nationally, there are 3 laboratories that have the ability to confirm cholera cases; the lack of laboratory capacity at HFs hampers case and outbreak confirmation. The absence of structured data analysis at the RPHD, HD, and HF further compounds the situation, making the goal of IDSR of data analysis and rapid response at the HD very challenging. Feedback is strongest at the central level (MoPH) and non-existent at the levels below it, with only minimal training and supervision of staff. In 2012, mobile phone coverage expanded to all 183 HDs and to HFs in 2014 in the Far North and North Regions. The phones improved immediate reporting and outbreak control. Further, the creation of cholera command and control centers, and introduction of laptops at all RPHDs are major strengths in the surveillance system. Completeness and timeliness of reporting varied considerably among levels. CONCLUSION: Significant milestones in the hierarchical structure towards integration and achieving early detection and rapid response in cholera surveillance are in effective use; however, some challenges exist. The surveillance system lack labs at HFs and there is no data analysis at HD level. Thus, the goal of IDSR-strategy of early detection, data analysis, and rapid response at the HD level is a challenge. Both human and material resources are needed at the HD level to achieve this goal.